O circuito curto de comercialização para o desenvolvimento rural: um estudo sobre as feiras-livres de Arapiraca, AL - Silva, Danielle Viturino da (2020)
The short commercialization circuit, although still in the consolidation phase of the theoretical framework, in Brazil, has several documented local, national and international initiatives. For the study context, the short commercialization circuit is considered a space responsible for direct transactions, which involve monetary values or not, where there is, the presence of even an intermediary. In view of the above, the objective of this work is to carry out a study on how a short commercialization circuit (CCC) contributes to rural development, having as an empirical reference the so-called “Popular Fairs of Family Farming”, located in the municipality of Arapiraca, in the countryside of Alagoas. For this, the quantitative and qualitative approaches were chosen, with several steps outlined: i) bibliographic review centered on five themes: modern agri-food system, short marketing circuits, open markets, family farming and research techniques; ii) recognition visits to the study areas, that is, to the two fairs in the municipality, iii) construction of the primary data collection instrument and its pre-test, iiii) field research, with the application of a questionnaire, conducting recorded interviews and direct observations on the spot. As a result, it was found that the fairs studied are presented as an important commercial space, as they are the spaces that enable the direct sale of products, without the presence of intermediaries, this scenario generates greater financial autonomy for farmers and family farmers. Finally, it can be said that these direct sales, still enabled an amplitude in the network of contacts of the marketers and the construction of relationships based on trust and reciprocity between producer and consumer.